The roles of the glycosylphosphatidylinositol anchor on the production and immunogenicity of recombinant ookinete surface antigen Pbs21 of Plasmodium berghei when prepared in a baculovirus expression system. - Martínez, A; Margos, G; Barker, G; Sinden, R (2000)
Malarial ookinetes express an immunodominant surface protein (P28) that is a priority candidate for the development of transmission-blocking vaccines. The full length P28 gene from Plasmodium berghei [Pbs21(1-213)] and a deletion construct [Pbs21(1-188)] encoding a protein that lacks the 25 C-terminal amino acids, including the glycosylphosphatidylinositol (GPI) anchor signal, were expressed in insect cells using baculovirus vectors. Pbs21(1-213) protein is strongly hydrophobic, found in the cytoplasm and on the surface of Spodoptera Sf21 cells, and in the culture medium. Pbs21(1-188) protein was largely found in the aqueous phase of the medium and in the cytoplasm of Sf21 cells, but was not detected on the cell surface. The presence of 25 C-terminal amino acids is therefore critical to the attachment of recombinant Pbs21 to the parasite plasma membrane. Mice were immunized subcutaneously or intramuscularly with affinity purified recombinant Pbs21(1-213), Pbs21(1-188) or native Pbs21 proteins. Following two immunizations, native Pbs21 induces higher titres when administered by either route, than the recombinant protein bearing an insect GPI anchor, which in turn is markedly more immunogenic than the recombinant polypeptide lacking a GPI anchor. When specific anti Pbs21 antibody titres exceeded 1 mg/ml all three antigens were capable of inducing transmission blockade > or = 90%, below 1 mg/ml blockade did not correlate with antibody concentration.